The Correlation Between Personality Types and Academic Performance Among ELT Students - Aini, Windy Nur; Sabarun; Widiastuty, Hesty (Prodi Tadris Bahasa Inggris, 2025)
This study investigates the correlation between extroversion, introversion, and academic performance in English Language Teaching (ELT). Using a quantitative correlational design, data were collected from 91 ELT students through MBTI-based personality assessments and GPA records. The results (Spearman’s rho = 0.08, p = 0.43) show no significant correlation, indicating that personality type alone does not determine academic success. Instead, learning strategies, motivation, and teaching methods play a more significant role. These findings highlight the importance of shifting from personality-based teaching to adaptable learning strategies that support students with diverse learning styles. Future research should explore how psychological and environmental factors interact to influence academic achievement in ELT contexts.